Idea- thematic basis in works of Li Bai - Anipina, A. K. (Journal of Oriental Studies, 2016)
Chinese poetry – one of the oldest national poetic traditions in the world. The immortal genius of poetry, Li Bai is one of the most respected poets in the history of Chinese literature and is one of the world’s major poets. Lyrics of Li Bai is typical for the whole of ancient Chinese poetry. The product of Li Bai’s extraordinary variety of different themes and genres, simple and expressive language, attention to human destiny. Classic of world literature, renewing and democratizing the Chinese poem, Li Bai had a decisive infl uence on the development of national poetry. Therefore, this research investigates the lyrical works of Li Bai, his lyrical imagery.